User Interface User Experience Design with User Centered Design Method On Mobile Application For Laundry KK Reservation - Lazuardy, Mika Aufasyah; Marie , Iveline Anne; Salim, Agus (Intelmatics, 2024)
Laundry KK is a business that offers kilogram laundry services established since November 2007, located at Jl. Kejaksaan No. 229A, Pondok Bambu East Jakarta, which provides several services such as dry cleaning, dry cleaning + ironing, bedsheet washing, and shoe cleaning. Currently, the service booking process at Laundry KK is still done manually, where customers have to visit the location to place their laundry orders. With the manual method, there are often issues such as missing or damaged laundry receipts, clothes being mixed up or lost due to transaction recording errors, and the business owner being unable to effectively track the transactions in the business. This research proposes the development of a user interface user experience (UI/UX) to simplify the process for the owner and users of Laundry KK services in creating an attractive interface design that captures the attention of consumers, providing an engaging user interface that makes it easy and interactive to book Laundry KK services. The end result of this research is the Prototype of the Laundry KK Ordering Application created using Figma, with the content features, menus, buttons, and text using the "Roboto" font. The design results were then subjected to a final evaluation with an average SUS score of 87.75, rating it as "Best Imaginable."